ChemInform Abstract: Tandem Catalysis in Domino Olefin Cross‐Metathesis/Intramolecular Oxa‐Conjugate Cyclization: Concise Synthesis of 2, 6‐cis‐Substituted Tetrahydropyran Derivatives. Issue 14 (20th March 2013) - Fuwa, Haruhiko; Noguchi, Takuma; Noto, Kenkichi; Sasaki, Makoto
Abstract Auto‐tandem as well as orthogonal‐tandem catalysis (OTC) are investigated in the preparation of the title compounds.